Staphylococcus aureus reservoirs and transmission routes in a Portuguese Neonatal Intensive Care Unit: a 30-month surveillance study. - Conceição, T (2013)
Although Staphylococcus aureus is a major cause of outbreaks in neonatal intensive care units (NICUs), there are no studies on the epidemiology of S. aureus isolates responsible for infection in Portuguese NICUs. Between July 2005 and December 2007, a total of 54 methicillin susceptible S. aureus (MSSA) isolates were recovered from 16 infected infants, parents, health care workers (HCWs), and the environment in a level III NICU. Isolates were characterized by pulsed-field gel electrophoresis (PFGE), spa typing, and multilocus sequence typing. Virulence determinants were detected by multiplex polymerase chain reaction. Three major MSSA clones were endemic in the NICU, representing 70% (n=38) of the isolates: PFGE type A-ST5 (n=17); type B-ST30 (n=12); and type C-ST1 (n=9). Leukotoxins and hemolysins were present in all isolates, although none of them carried PVL. HCWs, plastic folders protecting clinical files, and mothers' nipples were identified as potential reservoirs and/or vehicles of dissemination of S. aureus. Consequently, additional infection control measures were implemented in this NICU.